National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages THE PATIENT'S STANDPOINT Consider the position first from the standpoint of the nation and of the individual patient: (a) What is needed (as we have seen) is a service of preventative as well as curative medicine. But the family doctor, under present conditions, is not in a position to render such service ; he is bound to be a sickness-man rather than a health-man. Called in only when there is recognised ill-health, he has little chance of helping the fit to keep fit, or the near-to-fit to become quite fit. Moreover, it is difficult for the family doctor, under present conditions, to keep in sufficiently close touch with others who are in a better position than he is to prevent ill-health. During the past 50 years the nation has developed a wide range of public health services, which are manned by a new class of public health officer; but the family doctor has little opportunity of keeping in contact with these officers who work alongside of him. The curative and the preventive health services are not closely associated as they should be. (A) As we have already said, the nation needs a medical service which is comprehensive, covering all kinds of treatment that may be needed, and open to all, irrespective of capacity to pay. Here, again, we find that the system under which the family doctor now has to work cannot produce such a service. The family doctor, by himself, cannot provide a comprehensive service. Medical science is becoming so vast a field that specialisation becomes increasingly necessary ; the family doctor cannot be a specialist in everything. Medical diagnosis is becoming much more exact, but may often need the service of a specialist. Medical treatment is becoming much more efficient, with new apparatus at its command ; but in doing so it becomes more expensive. The general practitioner, who probably has only a small surgery to work in, cannot possibly bring together all these new resources of knowledge, skill, and apparatus for the service of the patient; only some kind of Health Centre, supported by the community, can do that. (c) Nor can the family doctor, by himself, supply a service that is truly open to all for very many of the people who need a doctor's attention, especially housewives and young people, are still debarred by poverty from going to him. Poverty makes a huge gap in the nation's health defences — a gap which not even the most devoted and self-sacrificing of doctor can fill by himself. To some extent this gap has been narrowed by the generosity of doctors, who often waive or reduce their fees for their poorer patients. It is obviously undesirable that a burden which should be the nation's should be borne in this way. To some extent, the gap is narrowed by the public provision of free medical services, such as treatment for tuberculosis and for venereal disease, free of charge where necessary; it is narrowed also by the Poor Law medical service, which makes some provision for the treatment of patients who are technically paupers. To a substantial extent also the gap is narrowed by the National Health Insurance Scheme, by which insured persons can secure certain medical attention and treatment from their panel doctor. (See page 8.) But still the gap between medical needs and medical service remains a wide one. It is particularly injurious in the case of children, who are not covered by the Insurance Scheme, and for whom the School Medical Service does not yet provide an adequate service. No mere tinkering with the system will close this gap. If we want a Medical Service which is open to all, comprehensive, preventive as well as curative, and based on relations of confidence between doctor and patient, we shall have to make some radical change in the present system of organising and paying for the service of home doctors. (d) These are not the only weaknesses of the existing system of family doctoring, from 7 36/H24/40